2009
DOI: 10.1021/la9037606
|View full text |Cite
|
Sign up to set email alerts
|

Doping-Induced Conductivity Transitions in Molecular Layers of Polyaniline: Optical Studies of Electronic State Changes

Abstract: The doping-induced conductivity transitions in molecular layers of polyaniline have been studied by monitoring the correlated optical and spectroscopic changes using spectroscopic and single wavelength extinction ellipsometry, also in total internal reflection mode (TIRE), together with reflection spectrometry. The measurements were performed on deposited multilayers as well as on a Langmuir monolayer at the air-water interface, as a function of acidic doping. We found that the characteristic spectroscopic fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 29 publications
2
18
0
Order By: Relevance
“…S4a †). 40,41 Different proton-doping levels between the previous work 38 and this work of ours can cause changes in the dielectric function. 39 Through electrodynamic simulations, we found that the peak shift caused by the reversible proton doping of PANI is increased with increasing dent depths (Fig.…”
Section: Resultsmentioning
confidence: 74%
“…S4a †). 40,41 Different proton-doping levels between the previous work 38 and this work of ours can cause changes in the dielectric function. 39 Through electrodynamic simulations, we found that the peak shift caused by the reversible proton doping of PANI is increased with increasing dent depths (Fig.…”
Section: Resultsmentioning
confidence: 74%
“…PA NI was treated as adielectric material with its dielectric function obtained from ar ecent report. [38] By adapting the varying dielectric constant into the COMSOL simulation package, our simulation shows that achange of the refractive index by 0.05 in NLO shell can induce aredshift as large as 20 nm in the scattering spectra for as ingle Au/PANI core/shell NR with the aspect ratio of 1.6 (Figure 5a). Ther edshift is also dependent on the thickness of the PA NI shell (Figure 5b).…”
Section: Angewandte Chemiementioning
confidence: 92%
“…The amplitude modulation depth is often calculated as the ratio or the dB value of the amplitude between the modulation and carrier waves. The dielectric functions measured in recent works [ 40 ] for the proton-doped and undoped states of PANI were employed for the simulations. [ 26,48 ] In our study, dB was employed.…”
Section: Doi: 101002/adma201305905mentioning
confidence: 99%
“…The solution was sucked away with a piece of fi lter paper after a certain period of time. [ 40 ] During the proton-doping (switching-off) process, PANI chains become positively charged, which results in slight chain expansion owing to electrostatic repulsion. Figure 3 a shows the spectral evolution of one representative (Au nanorod core)/(PANI shell) nanostructure from the 39-nm-shelled sample when the nanostructure was switched on.…”
Section: Doi: 101002/adma201305905mentioning
confidence: 99%
See 1 more Smart Citation